The impact of diversification on bank stability in India - Krishnan Chandramohan; CA Dipti Lunawat; CA Ajay Lunawat (Cogent Business & Management, 2022)
We study the concurrent impact of functional, geographic and loan portfolio diversification on the stability of commercial banks in India. The sample of 48 banks includes public sector banks, private sector banks and foreign banks operating in India. The unbalanced panel details operational and financial performance for the decade starting from 2007. We employed a dynamic Generalised Method of Moments (GMM) model to estimate the impact of diversification on bank stability. Two reasons justify the use of this approach. First, it incorporates the persistence in risk and stability, thus far neglected in diversification literature. Second, it addresses the concerns of endogeneity between diversification and stability. We find that all three dimensions of diversification, namely; functional, geographic and loan-portfolio diversification, improve bank stability. Apart from the methodological improvements, the multi-dimensional view of diversification adopted in this paper improves on the existing studies of Indian banks. Our analysis of Indian banks suggests that diversification has helped improve resilience. Our findings encourage policymakers and top management to pursue strategic functional, geographic and loan-portfolio diversification.
Keywords: G21; 650; Diversification; Bank Stability; Functional Diversification; Geographic Diversification; Indian Banking System; Loan portfolio diversification; Revenue Diversification